Investigating the impact of climate change on agricultural production in eastern and southern African countries - Belloumi, Mounir (International Food Policy Research Institute, 2014)
Climate change has been a significant issue since the end of the 20th century, and impacts a variety of economic sectors, primarily agriculture. The negative impacts of climate change on agricultural production are important because agriculture is closely linked to food security. Although they contribute the least to global pollution, it is estimated that African countries will be the most affected by climate variability. Our paper analyzes the impact of climate change on agricultural production in 11 Eastern and Southern African countries (ESA) during the period from 1961 to 2011 and estimates a panel data model for agricultural production using climate variables (e.g., annual precipitation and annual mean temperature) and economic factors (e.g., livelihood, fertilizer use, machinery, agricultural land, and labor) as explanatory variables.